STUDY OF CONTEXTUAL ARCHITECTURE CONCEPTS IN GOVERNMENT BUILDINGS - Baskoro, Mohamad; Hantono, Dedi (Universitas Telkom, 2022)
Contextual architecture is a concept in creating building designs and their aspects by taking into account the surrounding environment. The design of contextual architecture can make the design of buildings or areas sustainable with the surrounding environment, with new designs whose characteristics harmonize with the surrounding environment. However, contextual architecture can also conflict with components in the surrounding environment. The application of the concept of contextual architecture in this study takes precedent studies on the Constitutional Court Building. From the precedent study, the discussion will be analyzed through the seven principles of contextual architecture. This study aims to determine how context influences the architectural design of the DKI Jakarta Constitutional Court Office. It is hoped that the results can be a reference for planning and designing government buildings. This research was conducted in a government building that is likely to use the concept of contextual architecture. The research method used is descriptive qualitative by describing and identifying each point of the principles of contextual architecture. Keywords: Contextual, Constitutional Court, Contextual Principles.